Stochastic Differential Equations - Cecconi, Jaures; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
C. Doleans-Dade: Stochastic processes and stochastic differential equations.- A. Friedman: Stochastic differential equations and applications.- D.W. Stroock, S.R.S. Varadhan: Theory of diffusion processes.- G.C. Papanicolaou: Wave propagation and heat conduction in a random medium.- C. Dewitt Morette: A stochastic problem in Physics.- G.S. Goodman: The embedding problem for stochastic matrices.
C. Doleans-Dade: Stochastic processes and stochastic differential equations -- A. Friedman: Stochastic differential equations and applications -- D.W. Stroock, S.R.S. Varadhan: Theory of diffusion processes -- G.C. Papanicolaou: Wave propagation and heat conduction in a random medium -- C. Dewitt Morette: A stochastic problem in Physics -- G.S. Goodman: The embedding problem for stochastic matrices.
Keywords: Mathematics; Differential equations, partial; Distribution (Probability theory).; Mathematics; Probability Theory and Stochastic Processes; Partial Differential Equations